Use of sildenafil in an infant with persistent pulmonary hypertension secondary to lung and renal hypoplasia - a case report - Karen Lavie-Nevo; Kevin C. Harris; Joseph Y. Ting (BMC, 2019)
Abstract Background Premature preterm rupture of membranes (PPROM) is reported to be associated with high rates of neonatal mortality and morbidity. Sildenafil has been used in infants with persistent pulmonary hypertension of newborn (PPHN) due to congenital diaphragmatic hernia (CDH) and bronchopulmonary dysplasia (BPD). Recently, Sildenafil has been evaluated as an alternative or adjunctive pulmonary vasodilator. This case report illustrates the use of early sildenafil for PPHN and right ventricular dysfunction in an unusual setting of lung and renal hypoplasia. Case presentation A male infant was born at 37 weeks with a birth weight of 2840 g. Rupture of membranes developed at approximately 24 weeks of gestational age (GA). Bilateral small kidneys (< 2 standard deviations below average) were detected on ultrasound (US) examination at 30 weeks of gestation. The baby developed pneumothorax and pulmonary hypertensive crisis towards the end of the first day. An echocardiogram showed a dilated right ventricle, moderate right ventricular systolic dysfunction, hypoplastic pulmonary arteries and a large patent ductus arteriosus with bidirectional flow. The patient was sedated, paralyzed, and inhaled nitric oxide was administered to decrease the pulmonary resistance. In anticipation of persistent pulmonary hypertension due to the hypoplastic lungs and small calibre of pulmonary arteries, sildenafil was started on day of life (DOL) 5 at a dosage of 0.25 mg/kg/dose Q8H and gradually increased to 2 mg/kg/dose Q8H on DOL 9. The patient was finally extubated on DOL 7 and weaned off of non-invasive respiratory support on DOL 26. Sildenafil was gradually weaned beginning on DOL 21 and discontinued on DOL 48. Repeat echocardiogram assessment at 3 months showed complete resolution of PHT and right ventricular dilatation. Conclusions We describe the early use of sildenafil in treating pulmonary hypertension associated with lung and renal hypoplasia in a non-CDH patient. Following this treatment the patient made a full recovery from right ventricular dysfunction.